Best Management Practices for Equines in Natural Disasters: VM252/VM252, 2/2023 - Irvine, Kelsey M.; Phillips, Brandi K. (EDIS, 2023)
Creating personalized emergency plans for evacuating or sheltering-in-place with horses helps horse owners to be as prepared as possible when natural disasters occur. This publication discusses disaster-specific considerations, making a plan, water and feed, documentation, fence and pasture preparations, animal identification, vaccinations, insurance, what to expect at agricultural inspection station stops, and more. Written by Kelsey M. Irvine and Brandi K. Phillips, and published by the UF/IFAS Veterinary Medicine—Large Animal Clinical Sciences Department, February 2023.